2014
DOI: 10.1159/000358296
|View full text |Cite
|
Sign up to set email alerts
|

Nine-Year Follow-Up of Children with Atopic Dermatitis by General Practitioners

Abstract: The frequency of associated comorbidity and the cost of treatments in patients with atopic dermatitis (AD) followed up in primary care settings are poorly known. We carried out a retrospective cohort study on a longitudinal electronic medical records database of patients consulting a panel of general practitioners in France. All subjects with AD diagnosed during the first year of life were selected and matched with infants without the disease according to sex (1,163 vs. 1,163). Subjects were followed up for 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Our findings are in agreement with the French study of children with atopic eczema 5 and the Canadian, German, and American studies of children with asthma 6 8 described in the “Introduction” section, and extend their findings by describing total health service use, but also more detailed subtypes of health services, medications, and costs. Furthermore, our results confirm other studies showing that far from all children with atopic disease get specialized treatment, even though it is recommended.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in agreement with the French study of children with atopic eczema 5 and the Canadian, German, and American studies of children with asthma 6 8 described in the “Introduction” section, and extend their findings by describing total health service use, but also more detailed subtypes of health services, medications, and costs. Furthermore, our results confirm other studies showing that far from all children with atopic disease get specialized treatment, even though it is recommended.…”
Section: Discussionsupporting
confidence: 91%
“…A French study found increased use of prescribed medication and higher costs of general practitioner consultations and prescribed medication among children with atopic eczema compared with healthy controls. 5 A Canadian and a German study found increased likelihood of consultations with the general practitioner and of hospitalization among children with asthma compared with children without. 6 , 7 Finally, an American study of children with the same insurance found increased odds of using prescribed medication, outpatient hospital visits, emergency department visits, and hospitalization among children with asthma compared with children without.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of comorbidities (including ophthalmic complications) is reported to be significantly higher in infants with AD than in the control group (47% vs. 28%) [61]. Other sources estimate the frequency of ocular complications in AD to be approximately 16.7% [62].…”
Section: Childrenmentioning
confidence: 99%
“…A total of 26 studies (33%) were considered to have conducted a form of cost‐of‐illness study, one of which used a model developed in Excel (Microsoft, Redmond, WA, U.S.A.) . Most of these studies evaluated the cost of eczema within children, with only two papers stating explicitly that they were evaluating adults with eczema . Other papers did not specify the population age, with 11 stating a population of patients with eczema .…”
Section: Resultsmentioning
confidence: 99%